Hantavirus Infection: Anticipation of Zoonotic Disease in Indonesia - Indrawati Sendow; NLPI Dharmayanti; M Saepullah; RMA Adjid (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Recently, the evidence of Hantavirus infection in human and animals is increasing, and new Hantavirus strain has been identified. The disease causes clinical renal and lung disorders and fatal to human. The presence of new Hantavirus strain, lack of available quick and accurate diagnostic tool, asymptomatic clinical signs and paucity of disease information, will inhibit disease control especially in the developing countries. The paper describes Hantavirus disease and its epidemiology in developed and developing countries, including Indonesia and its recommendation for disease prevention and control.